2020
DOI: 10.4285/kjt.2020.34.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent parvovirus B19 infection-associated pure red cell aplasia in a kidney transplant patient

Abstract: Posttransplant anemia is a common complication after kidney transplantation. Parvovirus B19 (PVB19) infection can induce pure red cell aplasia (PRCA) in immunosuppressed transplant patients. We herein report a case of recurrent PVB19-associated PRCA in a kidney transplant patient. A 49-year-old woman presented with anemia and normal renal function 1 year after a deceased-donor kidney transplantation for immunoglobulin A nephropathy-related end-stage renal disease. She received desensitization therapy, and 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Gang et al reported a case of recurrent PB19‐related PRCA during 1‐year post‐renal transplantation, with 7 months duration between two anemic episodes. Although reducing tacrolimus with IVIG treatment improved the clinical condition at the first episode of anemia, ultimately switching from tacrolimus to cyclosporine improved the anemia and decreased the PB19 viral load 25 . Changing from tacrolimus to everolimus, a mTOR inhibitor, was found favorable for a KTR with recurrent anemia associated with chronic PB19 infection who did not first benefit from standard therapy 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gang et al reported a case of recurrent PB19‐related PRCA during 1‐year post‐renal transplantation, with 7 months duration between two anemic episodes. Although reducing tacrolimus with IVIG treatment improved the clinical condition at the first episode of anemia, ultimately switching from tacrolimus to cyclosporine improved the anemia and decreased the PB19 viral load 25 . Changing from tacrolimus to everolimus, a mTOR inhibitor, was found favorable for a KTR with recurrent anemia associated with chronic PB19 infection who did not first benefit from standard therapy 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although reducing tacrolimus with IVIG treatment improved the clinical condition at the first episode of anemia, ultimately switching from tacrolimus to cyclosporine improved the anemia and decreased the PB19 viral load. 25 Changing from tacrolimus to everolimus, a mTOR inhibitor, was found favorable for a KTR with recurrent anemia associated with chronic PB19 infection who did not first benefit from standard therapy. 26 However, Nowacka-Cieciura et al showed that the effectiveness of everolimus requires more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Immunsupprimierten treten insbesondere Zytopenien häufig auf. Die Ursachen dafür sind vielfältig, wobei die häufigsten Gründe Medikamentennebenwirkungen (bedingt durch Immunsuppression oder Toxizität) und/oder virale Infektionen sind [16,31] Im späteren Verlauf nach TX spielen auch hämatologische/onkologische Erkrankungen und Behandlungsregime eine Rolle. Exotisches Beispiel einer Anämie unter Immunsuppression ist die "Pure red Cell Aplasia" (isolierte, teils schwere Anämie) bei einer möglichen Parvovirus-B19-Infektion; aber auch hier sind mannigfaltige Ursachen (erworben/ Malignität/vererbt) möglich [31,32,33]…”
Section: Blutbildveränderungen: Zytopenienunclassified